Redisain Terminal Pesiapan Kabupaten Tabanan - Sudana, Ngurah Madhu; Acwin Dwijendra, Ngakan Ketut; Kastawan, I Wayan (Jurnal Arsitektur Universitas Udayana, 2021)
Along with the development of land transportation public transportation users are starting to decrease, slowly now where this is caused by several factors, namely incomplete facilities at the terminal and departure times which are often late from schedule. To overcome this, there are several factors that influence it, including social, culture, environmental and climatic. Social conditions are an operational management in terms of quality and quantity. In terms of socio-cultural factors based on the Hindu religion that grows and develops in the community of Tabanan Regency. From an environment and climate, the planned building can adapt to the local climate and environment. In the sense that it does not damage the environment and can take advantage of the potential of the existing climate and environment so that it can maintain sustainability and harmony with its surroundings. n terms of these factors, interlocking space is an architecture that puts forward the maximum visual communication relationship function. Where the potential exists in the area with supporting facilities in the terminal needed to add public and supporting facilities, as well as providing convenience for visitors by rearranging circulation, zoning and vegation in order to support terminal facilities and support the terminal as a transportation attraction in Tabanan Regency. This paper used combination of design methods and research methods in the collection and processing of data related to the design. Keywords: Social, Culture, Environment, Climate